Precautionary Measures Conditions - Anas Bin Dhafer Ali Al-Omari (International Journal of Law Research and Studies, 2025)
This thesis aims to explain and review precautionary measures, including their types and applications in the Saudi system. It also attempts to classify them, explain their concepts, and extract the legal texts regulating them in the various Saudi criminal laws and regulations, in addition to other related laws that address these measures in their texts. In addition to extracting legal texts that dealt with this topic in other comparative systems, such as the French system, the Egyptian system, the Lebanese system, and the Algerian system. This study initially dealt with the definition of precautionary measures, their concept, and their historical emergence, in the introductory chapter. It also dealt with the nature of these measures, by explaining the conditions for their application, their nature and provisions, and the distinction between them and traditional punishment, in the first chapter. The second chapter was devoted to reviewing the types of precautionary measures, by classifying them into personal precautionary measures and material precautionary measures, with a statement of what was stated in the Saudi system and comparative systems of texts that addressed this matter according to each type.